A hemodialysis catheter and a method for preparing the same
The extrusion process of using porous materials loaded with antibacterial substances and carrier materials in the hemodialysis catheters is solved by solving the problems of poor biocompatibility and toxicity risks of catheters, achieving higher biocompatibility and antibacterial properties.
Patent Information
- Application Number
- CN202411921275.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing hemodialysis catheter has poor biocompatibility and there is a risk of toxicity in long-term use.
The hemodialysis catheter is made by extrusion process using porous materials and carrier materials loaded with antibacterial substances. The porous materials are loaded by antibacterial agents and obtained by oxidation and reduction reactions. The mass fraction of the antibacterial substances is 1%-5%.
It improves the biocompatibility of the hemodialysis catheter, reduces biotoxicity, prolongs the antibacterial time, avoids the risk of thrombosis, and improves the antibacterial performance of the catheter.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical devices, and in particular to a hemodialysis catheter and a preparation method thereof. Background Art
[0002] Hemodialysis catheters are a type of medical device widely used in a variety of medical fields. They are mainly used for long-term or short-term delivery, drainage, and monitoring of body fluids. These catheters can be implanted in a variety of locations. The development of materials science, bioengineering, information technology, and minimally invasive surgery has promoted the application of hemodialysis catheters in more medical fields. In order to adapt to the use of hemodialysis catheters in multiple fields, more and more new materials are being introduced into the manufacture of hemodialysis catheters to improve patients' treatment experience and quality of life. However, long-term use or implantation of hemodialysis catheters can cause persistent infections due to problems such as long catheter retention time, bacterial colonization on the catheter surface and surrounding tissues, and the formation of biofilms. This not only causes patients to suffer and prolongs their hospital stay, but can also be life-threatening in severe cases.
[0003] The prior art discloses an antibacterial and anticoagulant central venous catheter and a preparation method thereof, wherein chitosan particles and silver ions are attached to the inner and outer surfaces of a polyurethane catheter, and the resulting catheter has an antibacterial effect. However, the catheter has poor biocompatibility and there is a risk of toxicity in long-term use. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the technical defects of the prior art hemodialysis catheter, that is, the poor biocompatibility and the risk of toxicity after long-term use, thereby providing a hemodialysis catheter and a preparation method thereof.
[0005] In one aspect, the present invention provides a hemodialysis catheter, comprising the following raw materials in parts by weight extruded through an extrusion process:
[0006] 1-10 parts of porous material loaded with antibacterial substances and 90-99 parts of carrier material, wherein the carrier material comprises a high molecular polymer,
[0007] The porous material loaded with antibacterial substances is obtained by loading an antibacterial agent on the porous material to undergo oxidation and reduction reactions. The mass fraction of the antibacterial substance in the porous material loaded with antibacterial substances is 1%-5%.
[0008] In order to further improve the antibacterial effect of the hemodialysis catheter and avoid the risk of thrombosis during use of the hemodialysis catheter, in some embodiments, the porous material provided by the present invention has the function of emitting infrared rays, and the wavelength of the infrared rays emitted by the porous material is 2μm-20μm.
[0009] Preferably, the porous material is at least one of graphite, graphene, tourmaline, cordierite, zirconium oxide, aluminum oxide, ferrosoferric oxide, silicon carbide and ceramic materials.
[0010] It should be noted that the porous material in the present invention can be made of at least one of graphite, graphene, tourmaline, cordierite, zirconium oxide, aluminum oxide, ferroferric oxide, silicon carbide and ceramic materials by conventional technical means. The preparation method of the porous material can be a template method, a foam method, a sol-gel method, a particle accumulation method and a direct foaming method. It can also be a porous material prepared by doping with specific elements. The present invention does not limit the preparation method of the porous material, as long as it can load the antibacterial material and can play a sustained release role.
[0011] Preferably, the porosity of the porous material of the present invention is 25%-95%.
[0012] Furthermore, in the present invention, the porosity of graphite and graphene is 80%-95%, the porosity of tourmaline is 75%-90%, the porosity of cordierite is 60%-80%, the porosity of zirconia is 25%-50%, the porosity of alumina is 30%-70%, the porosity of ferrosoferric oxide is 30%-60%, the porosity of silicon carbide is 25%-45%, and the porosity of ceramic materials is 50%-75%.
[0013] In some embodiments, the antibacterial agent is an inorganic salt, and the cation in the inorganic salt is at least one of silver ions, zinc ions or copper ions.
[0014] The inorganic salt whose cation is copper ion is at least one of copper nitrate, copper sulfate, copper chloride or copper carbonate; and / or,
[0015] The inorganic salt whose cation is a silver ion is at least one of silver nitrate, silver sulfate, silver chloride or silver carbonate; and / or,
[0016] The inorganic salt whose cation is zinc ion is at least one of zinc nitrate, zinc sulfate, zinc chloride or zinc carbonate.
[0017] The reducing agent in the reduction reaction is at least one of hydrogen or carbon monoxide.
[0018] The high molecular polymer includes at least one of silicone rubber and polyurethane.
[0019] The polyurethane also includes modified polyurethane, which is a material obtained by physically or chemically modifying polyurethane using conventional technical means.
[0020] In another aspect, the present invention provides a method for preparing the above-mentioned hemodialysis catheter, comprising the following steps:
[0021] S1, attaching an antibacterial agent to the surface of a porous material to obtain a first mixture;
[0022] S2, heat-treating the first mixture under an oxygen atmosphere to obtain a second mixture;
[0023] S3, heat-treating the second mixture in the presence of a reducing agent to obtain a porous material loaded with an antibacterial substance;
[0024] S4, mixing the porous material loaded with the antibacterial substance with the carrier material, and extruding them to form a hemodialysis catheter.
[0025] In some embodiments, in step S1, the step of attaching the antibacterial agent to the surface of the porous material is specifically to immerse the porous material in a solution containing the antibacterial agent, separate the solid from the liquid, and immerse at a temperature of 50°C-100°C for a time of 10min-30min.
[0026] Preferably, the ratio of the antibacterial agent to the porous material is (1-5):(5-20), in units of mol:g.
[0027] Preferably, the solid-liquid separation step in step S1 is filtering and drying, wherein the drying temperature is 60°C-100°C.
[0028] In some embodiments, the antibacterial agent is an inorganic salt, the cation in the inorganic salt is at least one of silver ions, zinc ions or copper ions, and the concentration of the cation in the solution containing the antibacterial agent is 0.5 mol / L-8 mol / L.
[0029] In some embodiments, the heat treatment temperature in step S2 is 300° C.-700° C., and the heat treatment time is 45 min-75 min.
[0030] In some embodiments, the heat treatment temperature in step S3 is 300° C.-500° C., and the heat treatment time is 45 min-75 min.
[0031] In some of the embodiments, in step S4, the porous material loaded with the antibacterial substance is mixed with the carrier under stirring, the stirring speed is 50 rpm-300 rpm, and the stirring time is 0.5 min-6 h.
[0032] In some embodiments, the temperature during extrusion in step S4 is 170°C-220°C.
[0033] Meanwhile, the present invention also provides a medical device or a medical implant, comprising the above-mentioned hemodialysis catheter or the hemodialysis catheter prepared by the above-mentioned method for preparing the hemodialysis catheter.
[0034] The technical solution of the present invention has the following advantages:
[0035] 1. A hemodialysis catheter provided by the present invention comprises the following raw materials extruded by weight, 1-10 parts of a porous material loaded with an antibacterial substance and 90-99 parts of a carrier material, wherein the carrier material comprises a high molecular polymer, the porous material loaded with an antibacterial substance is obtained by oxidation and reduction reaction of an antibacterial agent loaded on a porous material, and the mass fraction of the antibacterial substance in the porous material loaded with an antibacterial substance is 1%-5%. The present invention loads the antibacterial substance on the surface of the porous material through a reduction reaction, and simultaneously utilizes the porous material loaded with the antibacterial substance and the carrier material to form a hemodialysis catheter through an extrusion process, and the hemodialysis catheter has the function of slow-release antibacterial material, which can not only prolong the antibacterial time, but also avoid the problem of biological toxicity caused by releasing a large amount of antibacterial material in a short time, thereby improving the biocompatibility of the hemodialysis catheter and reducing biological toxicity.
[0036] 2. The present invention provides a hemodialysis catheter, wherein the porous material emits infrared light with a wavelength of 2μm-20μm. After the hemodialysis catheter is implanted, thrombosis is easily caused due to problems such as vascular endothelial damage, local blood flow near the catheter, infection, and long retention time. In order to reduce the risk of thrombosis, the present invention selects a hemodialysis catheter made of a porous material that emits infrared light with a wavelength of 2μm-20μm, and improves the blood flow rate and promotes blood circulation through the infrared function of the porous material. Through the photobiomodulation effect, cell activity is stimulated to promote wound healing and tissue repair. At the same time, the antibacterial effect of the hemodialysis catheter is used to reduce the occurrence of inflammation and avoid the formation of thrombosis after the hemodialysis catheter is implanted. The porous material has high biocompatibility, and the use of a porous material with infrared emission function can further improve the antibacterial properties of the hemodialysis catheter.
[0037] 3. A method for preparing a hemodialysis catheter provided by the present invention comprises the following steps: S1, attaching an inorganic salt solution to the surface of a porous material to obtain a first mixture; S2, heat-treating the first mixture under an oxygen atmosphere to obtain a second mixture; S3, heat-treating the second mixture in the presence of a reducing agent to obtain a porous material loaded with an antibacterial substance; S4, mixing the porous material loaded with the antibacterial substance with a carrier material, and extruding and molding the mixture into a hemodialysis catheter. The preparation method provided by the present invention is easy to operate and is conducive to large-scale production. DETAILED DESCRIPTION
[0038] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0040] The polyurethane in the embodiment of the present invention is purchased from Lubrizol and its brand is Pellethane. ® 2363-65D, silicone rubber purchased from Beiteli, brand SH-2250A / B.
[0041] The tourmaline in the present invention is purchased from Pengxian Mineral Products Processing Factory in Lingshou County. The infrared wavelength emitted by the tourmaline at room temperature is 2-18 μm.
[0042] Example 1
[0043] This embodiment provides a method for preparing a hemodialysis catheter, and the specific steps and parameters are as follows:
[0044] (1) 10 g of tourmaline is soaked in 500 mL of a 5 mol / L copper nitrate aqueous solution at 80° C. for 20 min. The residue obtained after filtration is dried at 80° C. to obtain tourmaline with copper ions attached thereto;
[0045] (2) treating the tourmaline with copper ions attached obtained in step (1) at 500° C. for 60 min in an oxygen atmosphere to obtain tourmaline with copper oxide attached;
[0046] (3) treating the tourmaline with copper oxide attached obtained in step (2) at 400° C. for 60 min in a hydrogen atmosphere to obtain tourmaline loaded with nano-copper.
[0047] The content of nano-copper in tourmaline loaded with nano-copper was determined by inductively coupled plasma technology (ICP) to be 4wt%;
[0048] (4) Take 5 g of nano-copper-loaded tourmaline prepared in step (3) and mix it with 95 g of polyurethane at a speed of 100 rpm for 60 min. Use an extruder to extrude and mold the blend at 200° C. to prepare a hemodialysis catheter.
[0049] Example 2
[0050] This embodiment provides a method for preparing a hemodialysis catheter. The specific steps and parameters are the same as those in Embodiment 1, except that the copper nitrate in step (1) is replaced by silver nitrate of equal volume and equal molar concentration.
[0051] Example 3
[0052] This embodiment provides a method for preparing a hemodialysis catheter. The specific steps and parameters are the same as those in Embodiment 1, except that zinc nitrate of equal volume and equal molar concentration is used to replace the copper nitrate in step (1).
[0053] Example 4
[0054] This embodiment provides a method for preparing a hemodialysis catheter. The specific steps and parameters are the same as those in Embodiment 1, except that a ceramic material of equal mass is used to replace the tourmaline in step (1).
[0055] Example 5
[0056] This embodiment provides a method for preparing a hemodialysis catheter. The specific steps and parameters are the same as those in Embodiment 1, except that an equal mass of aluminum oxide is used to replace the tourmaline in step (1).
[0057] Example 6
[0058] This embodiment provides a method for preparing a hemodialysis catheter. The specific steps and parameters are the same as those in Embodiment 1, except that an equal mass of zirconium oxide is used to replace the tourmaline in step (1).
[0059] Example 7
[0060] This embodiment provides a method for preparing a hemodialysis catheter. The specific steps and parameters are the same as those in Embodiment 1, except that an equal mass of graphite is used to replace the tourmaline in step (1).
[0061] Example 8
[0062] This embodiment provides a method for preparing a hemodialysis catheter. The specific steps and parameters are the same as those in Embodiment 1, except that an equal mass of graphene is used to replace the tourmaline in step (1).
[0063] Example 9
[0064] This embodiment provides a method for preparing a hemodialysis catheter, and the specific steps and parameters are as follows:
[0065] (1) 1 g of tourmaline is soaked in 2000 mL of a 0.5 mol / L copper nitrate aqueous solution at 80° C. for 20 min. The residue obtained after filtration is dried at 80° C. to obtain tourmaline with copper ions attached thereto;
[0066] (2) treating the tourmaline with copper ions attached obtained in step (1) at 500° C. for 60 min in an oxygen atmosphere to obtain tourmaline with copper oxide attached;
[0067] (3) treating the tourmaline with copper oxide attached obtained in step (2) at 400° C. for 60 min in a hydrogen atmosphere to obtain tourmaline loaded with nano-copper.
[0068] The content of nano-copper in tourmaline loaded with nano-copper was determined by inductively coupled plasma technology (ICP) to be 3wt%;
[0069] (4) Take 5 g of nano-copper-loaded tourmaline prepared in step (3) and mix it with 95 g of polyurethane at a speed of 100 rpm for 60 min. Use an extruder to extrude and mold the blend at 200° C. to prepare a hemodialysis catheter.
[0070] Example 10
[0071] This embodiment provides a method for preparing a hemodialysis catheter, and the specific steps and parameters are as follows:
[0072] (1) 20 g of tourmaline is soaked in 2500 mL of 8 mol / L copper nitrate aqueous solution at 80° C. for 20 min. The filter residue obtained after filtration is dried at 80° C. to obtain tourmaline with copper ions attached thereto;
[0073] (2) treating the tourmaline with copper ions attached obtained in step (1) at 500° C. for 60 min in an oxygen atmosphere to obtain tourmaline with copper oxide attached;
[0074] (3) treating the tourmaline with copper oxide attached obtained in step (2) at 400° C. for 60 min in a hydrogen atmosphere to obtain tourmaline loaded with nano-copper.
[0075] The content of nano-copper in tourmaline loaded with nano-copper was determined by inductively coupled plasma technology (ICP) to be 5wt%;
[0076] (4) Take 5 g of nano-copper-loaded tourmaline prepared in step (3) and mix it with 95 g of polyurethane at a speed of 100 rpm for 60 min. Use an extruder to extrude and mold the blend at 200° C. to prepare a hemodialysis catheter.
[0077] Embodiment 11
[0078] This embodiment provides a method for preparing a hemodialysis catheter, and the specific steps and parameters are as follows:
[0079] (1) 10 g of tourmaline was soaked in 500 mL of a 5 mol / L copper nitrate aqueous solution at 50° C. for 30 min. The residue obtained after filtration was dried at 60° C. to obtain tourmaline with copper ions attached thereto;
[0080] (2) treating the tourmaline with copper ions attached obtained in step (1) at 300° C. for 75 min in an oxygen atmosphere to obtain tourmaline with copper oxide attached;
[0081] (3) treating the tourmaline with copper oxide attached obtained in step (2) at 500° C. for 45 min in a carbon monoxide atmosphere to obtain tourmaline loaded with nano-copper.
[0082] The content of nano-copper in tourmaline loaded with nano-copper was determined by inductively coupled plasma technology (ICP) to be 4wt%;
[0083] (4) Take 1 g of nano-copper-loaded tourmaline prepared in step (3) and mix it with 99 g of polyurethane at 300 rpm for 60 min. Use an extruder to extrude and mold the mixture at 220° C. to prepare a hemodialysis catheter.
[0084] Example 12
[0085] This embodiment provides a method for preparing a hemodialysis catheter, and the specific steps and parameters are as follows:
[0086] (1) 10 g of tourmaline is soaked in 500 mL of a 5 mol / L copper nitrate aqueous solution at 100° C. for 10 min. The filter residue obtained after filtration is dried at 100° C. to obtain tourmaline with copper ions attached thereto;
[0087] (2) in an oxygen atmosphere, treating the tourmaline with copper ions attached thereto obtained in step (1) at 700° C. for 45 minutes to obtain tourmaline with copper oxide attached thereto;
[0088] (3) treating the tourmaline with copper oxide attached obtained in step (2) at 300° C. for 75 min in a hydrogen atmosphere to obtain tourmaline loaded with nano-copper.
[0089] The content of nano-copper in tourmaline loaded with nano-copper was determined by inductively coupled plasma technology (ICP) to be 4wt%;
[0090] (4) Take 10 g of nano-copper-loaded tourmaline prepared in step (3) and mix it with 90 g of silicone rubber at a rotation speed of 500 rpm for 6 h. Use an extruder to extrude and mold the blend at 170° C. to prepare a hemodialysis catheter.
[0091] Comparative Example 1
[0092] This comparative example provides a method for preparing a hemodialysis catheter, and the specific steps and parameters are as follows:
[0093] (1) 10 g of graphite was immersed in 500 mL of a 5 mol / L copper nitrate aqueous solution, and the residue obtained after filtration was dried at 80° C. to obtain graphite with copper ions attached thereto;
[0094] (2) treating the graphite with copper ions attached obtained in step (1) at 500° C. for 60 min in an oxygen atmosphere to obtain graphite with copper oxide attached;
[0095] (3) 5 g of the graphite loaded with nano-copper prepared in step (2) was mixed with 95 g of polyurethane at a rotation speed of 100 rpm for 60 min, and the mixture was extruded and molded into a hemodialysis catheter at 200 °C using an extruder.
[0096] Comparative Example 2
[0097] This comparative example provides a method for preparing a hemodialysis catheter, and the specific steps and parameters are as follows:
[0098] 5 g of graphite was mixed with 95 g of polyurethane at a rotation speed of 100 rpm for 60 min, and extruded in an extruder at 200° C. to prepare a hemodialysis catheter.
[0099] Comparative Example 3
[0100] This comparative example provides a method for preparing a hemodialysis catheter, and the specific steps and parameters are as follows:
[0101] (1) 10 g of graphite was immersed in 500 mL of a 5 mol / L copper nitrate aqueous solution, and the residue obtained after filtration was dried at 80° C. to obtain graphite with copper ions attached thereto;
[0102] (2) treating the graphite with copper ions attached obtained in step (1) at 500° C. for 60 min in an oxygen atmosphere to obtain graphite with copper oxide attached;
[0103] (3) treating the graphite with copper oxide attached obtained in step (2) at 400° C. for 60 min in a hydrogen atmosphere to obtain graphite loaded with nano-copper;
[0104] The content of nano-copper in tourmaline loaded with nano-copper was determined by inductively coupled plasma technology (ICP) to be 4wt%;
[0105] (4) 95 g of polyurethane was extruded and molded into a catheter at 200° C. using an extruder, 5 g of graphite loaded with nano-copper prepared in step (3) was mixed with 10 mL of water to form a coating solution, the coating solution was dip-coated on the surface of the hemodialysis catheter, and the solution was dried at 80° C. to obtain a hemodialysis catheter.
[0106] Comparative Example 4
[0107] This embodiment provides a method for preparing a hemodialysis catheter, and the specific steps and parameters are as follows:
[0108] (1) 10 g of graphite was soaked in 1000 mL of a 5 mol / L copper nitrate aqueous solution at 80° C. for 20 min. The residue obtained after filtration was dried at 80° C. to obtain graphite with copper ions attached thereto;
[0109] (2) treating the graphite with copper ions attached obtained in step (1) at 500° C. for 60 min in an oxygen atmosphere to obtain graphite with copper oxide attached;
[0110] (3) treating the copper oxide-attached graphite obtained in step (2) at 400° C. for 60 min in a hydrogen atmosphere to obtain graphite loaded with nano-copper.
[0111] The content of nano-copper in the graphite loaded with nano-copper was determined by inductively coupled plasma technology (ICP) to be 6wt%;
[0112] (4) Take 5 g of graphite loaded with nano-copper prepared in step (3) and mix it with 95 g of polyurethane at a speed of 100 rpm for 60 min. Use an extruder to extrude and mold the mixture at 200° C. to form a hemodialysis catheter.
[0113] Experimental Example 1
[0114] The antibacterial properties of the hemodialysis catheters prepared in Examples 1-12 and Comparative Examples 1-3 of the present invention were measured with reference to ISO 22196-2011 “Evaluation method for antibacterial properties of plastic products”. At the same time, in order to detect the long-term antibacterial properties of the hemodialysis catheters prepared in each embodiment and comparative example, the test sample was immersed in a distilled water solution at 37° C. The immersion time was 1 day, 5 days, 10 days, 20 days and 30 days, respectively. The antibacterial properties of the surface of the hemodialysis catheter after immersion for different days were measured. The results are shown in Table 1, wherein the antibacterial activity standard was adopted for the antibacterial rate of Escherichia coli or the antibacterial rate of Staphylococcus aureus. The antibacterial rate of the hemodialysis catheters for different immersion times was % = (the average logarithmic value of the number of bacteria per unit area of the untreated sample-the average logarithmic value of the number of bacteria per unit area of the treated sample) / the average logarithmic value of the number of bacteria per unit area of the untreated sample.
[0115] Table 1 Antibacterial properties of hemodialysis catheter surface
[0116]
[0117] According to Table 1, compared with Comparative Example 2, the hemodialysis catheter prepared without adding antibacterial materials has poor antibacterial performance. Comparative Example 1 uses divalent copper as the antibacterial material, and Comparative Example 3 uses a coating method to load monovalent copper ions. Although the short-term antibacterial effect is good, it does not have a long-term antibacterial effect. The hemodialysis catheter provided by the embodiment of the present invention not only has a good antibacterial effect, but also has a long-term effect.
[0118] Experimental Example 2
[0119] The in vitro cytotoxicity of the hemodialysis catheters prepared in Examples 1-12 and Comparative Examples 1-3 of the present invention at different treatment times was tested with reference to the method of GB / T 16886.5-2017 "Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Test", wherein the different treatment times refer to immersing the hemodialysis catheters in a distilled water solution at 37° C., specifically immersing for 1 day, 5 days, 10 days, 20 days and 30 days, and measuring the in vitro cytotoxicity of the hemodialysis catheters after immersion for different days. The test results are shown in Table 2, wherein grades 0 and 1 meet the requirements of biomedical materials.
[0120] Table 2 In vitro cytotoxicity of hemodialysis catheters
[0121]
[0122] According to the data in Table 2, the hemodialysis catheter provided in Comparative Example 1 with divalent copper as an antibacterial agent is highly toxic, because divalent copper can bind to proteins, enzymes and nucleic acids, and also has the problem of damaging cell membranes and affecting cell metabolism. At the same time, divalent copper is also a strong oxidant that catalyzes the generation of free radicals and damages cell structure and function. Comparative Example 3 uses a coating method to coat monovalent copper on the surface of the hemodialysis catheter. As the immersion time changes, it will cause an increase in cytotoxicity. When the content of antibacterial substances in Comparative Example 4 is 6wt%, the toxicity is weak in the short term, but due to the high content of monovalent copper, there is a problem of accumulation of monovalent copper. As time goes by, the toxicity increases, and the content of monovalent copper ions is too high, which also leads to an increase in the color opacity of the hemodialysis catheter, affecting the observation effect in the use of hemodialysis. The hemodialysis catheter provided by the present invention has low in vitro cytotoxicity, and there is no problem of long-term accumulation. It will not cause cytotoxicity during use, indicating that the hemodialysis catheter provided by the present invention has good biocompatibility.
[0123] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A hemodialysis catheter, characterized in that: The following raw materials in parts by weight are extruded through an extrusion process: 1-10 parts of porous material loaded with nano-scale antibacterial substances and 90-99 parts of carrier material, wherein the carrier material comprises a high molecular polymer, The porous material loaded with nano-scale antibacterial substances is obtained by loading an antibacterial agent on the porous material to undergo oxidation and reduction reactions, and the mass fraction of the nano-scale antibacterial substances in the porous material loaded with nano-scale antibacterial substances is 4%; The porous material is tourmaline; The antibacterial agent is copper nitrate; The method for preparing the hemodialysis catheter comprises the following steps: S1, attaching the antibacterial agent to the surface of the porous material to obtain a first mixture, wherein the ratio of the antibacterial agent to the porous material is (1-5):(5-20), in units of mol:g; S2, heat-treating the first mixture in an oxygen atmosphere to obtain a second mixture, wherein the heat-treating temperature is 300° C.-700° C. and the heat-treating time is 45 min-75 min; S3, heat-treating the second mixture in the presence of a reducing agent to obtain a porous material loaded with nano-scale antibacterial substances, wherein the heat-treating temperature is 300° C.-500° C. and the heat-treating time is 45 min-75 min; S4, mixing, extruding and molding the porous material loaded with nano-scale antibacterial substances with the carrier material into a hemodialysis catheter.
2. The hemodialysis catheter according to claim 1, characterized in that: The wavelength of infrared light emitted by the porous material is 2 μm-20 μm.
3. The hemodialysis catheter according to claim 2, characterized in that: The high molecular polymer includes at least one of silicone rubber and polyurethane.
4. The hemodialysis catheter according to claim 3, characterized in that: The reducing agent in the reduction reaction is at least one of hydrogen or carbon monoxide.
5. A method for preparing a hemodialysis catheter according to any one of claims 1 to 4, characterized in that: The following steps are included: S1, attaching an antibacterial agent to the surface of a porous material to obtain a first mixture; S2, heat-treating the first mixture under an oxygen atmosphere to obtain a second mixture; S3, heat-treating the second mixture in the presence of a reducing agent to obtain a porous material loaded with nano-scale antibacterial substances; S4, mixing, extruding and molding the porous material loaded with nano-scale antibacterial substances with the carrier material into a hemodialysis catheter.
6. The preparation method according to claim 5, characterized in that: In step S1, the step of attaching the antibacterial agent to the surface of the porous material is specifically to immerse the porous material in a solution containing the antibacterial agent, separate the solid from the liquid, and immerse at a temperature of 50°C to 100°C for a time of 10 min to 30 min. The ratio of antimicrobial agent to porous material is (1-5):(5-20), in mol:g; The concentration of cations in the solution containing the antimicrobial agent is 0.5 mol / L-8 mol / L; The temperature of the heat treatment in step S2 is 300° C.-700° C., and the time of the heat treatment is 45 min-75 min.
7. The preparation method according to claim 6, characterized in that: The solid-liquid separation step in step S1 is filtering and drying, wherein the drying temperature is 60°C-100°C; The temperature of the heat treatment in step S3 is 300° C.-500° C., and the time of the heat treatment is 45 min-75 min.
8. The preparation method according to claim 7, characterized in that: In step S4, the porous material loaded with the antibacterial substance is mixed with the carrier under stirring, the stirring speed is 50 rpm-300 rpm, and the stirring time is 0.5 min-6 h. The temperature during extrusion is 170°C-220°C.
9. A medical device or a medical implant, characterized in that The invention comprises the hemodialysis catheter according to any one of claims 1 to 4 or the hemodialysis catheter prepared by the method for preparing the hemodialysis catheter according to any one of claims 5 to 8.
Citation Information
Patent Citations
Slowly released type antibiotic medical catheter and preparation method thereof
CN101361991A
Preparation method of silver-copper metal colloid activated carbon antibacterial agent and organic artificial stone thereof
CN111903710A
Preparations and Applications of Composite ofAntibiotic Silver and Tourmaline
KR1020020063533A